2011
DOI: 10.1007/s11243-011-9562-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sacrificial electron donors on hydrogen generation over visible light–irradiated nonmetal-doped TiO2 photocatalysts

Abstract: Hydrogen generation over carbon-, nitrogenand sulfur-doped TiO 2 semiconductor photocatalysts (represented as C-TiO 2 , N-TiO 2 and S-TiO 2 , respectively) under visible light irradiation has been achieved using various sacrificial electron donors, namely triethanolamine, diethanolamine, monoethanolamine, triethylamine, MeOH, EtOH, EDTA, L-ascorbic acid and phenol. The highest initial rate of H 2 production was found to be in the range 1,000-2,200 lmol/g/h at ambient conditions when triethanolamine was used as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 22 publications
2
24
0
Order By: Relevance
“…Thus, the observed results suggest that the efficiency of the selected SED is not only dictated by its thermodynamic ability to reduce the oxidized pho- tosensitizer,b ut also by the kinetic barrier for the electron transfer process. In this regard,i th as been already observed that TEOA is am ore efficient hole scavenger than methanol or ethanol in photocatalyticH 2 generation processes by using inorganic [54,55] or carbon-based catalysts, [56] and this difference has been ascribed to the fact that TEOA can use the lone pair of nitrogen for the first electron transfer, [57] in agreement with earlier reports indicating that only the deprotonated form of the amine is an activer educing agent. [43] Based on relevant literature references on TEOA [58] and alcohol photoreforming, [3,5,10,14] am echanistic proposal for the two different regeneration processes is presented in Figure S10 in the Supporting Information, bearing in mind that in this instancen op hotogenerated holes are present on TiO 2 owing to the filtering of simulated solar light.…”
Section: Resultssupporting
confidence: 88%
“…Thus, the observed results suggest that the efficiency of the selected SED is not only dictated by its thermodynamic ability to reduce the oxidized pho- tosensitizer,b ut also by the kinetic barrier for the electron transfer process. In this regard,i th as been already observed that TEOA is am ore efficient hole scavenger than methanol or ethanol in photocatalyticH 2 generation processes by using inorganic [54,55] or carbon-based catalysts, [56] and this difference has been ascribed to the fact that TEOA can use the lone pair of nitrogen for the first electron transfer, [57] in agreement with earlier reports indicating that only the deprotonated form of the amine is an activer educing agent. [43] Based on relevant literature references on TEOA [58] and alcohol photoreforming, [3,5,10,14] am echanistic proposal for the two different regeneration processes is presented in Figure S10 in the Supporting Information, bearing in mind that in this instancen op hotogenerated holes are present on TiO 2 owing to the filtering of simulated solar light.…”
Section: Resultssupporting
confidence: 88%
“…XRD data were collected from 2h = 10-90°(step 0.02°, scan rate 2°min À1 ) using Cu Ka X-rays (k = 1.5418 Å, 40 mA, 40 kV). Anatase, brookite and rutile crystallite sizes (L) were determined from the powder XRD data using the Scherrer equation and line-widths of the anatase (1 0 1) reflection at 2h = 25.3°, the brookite (1 2 1) reflection at 2h = 30.8°a nd rutile (1 1 0) reflection at 2h = 27.4°, respectively [28,40]. The rutile:anatase ratio in P25 TiO 2 was determined according to the method described by Ding et al [44].…”
Section: Au/tio 2 Photocatalyst Synthesismentioning
confidence: 99%
“…Interestingly, Ni-Ag(3.0)@C-TiO2 demonstrated remarkable high conversion of MB both under UV and visible irradiations. These results suggest that the synergistic action between C dopant and bimetallic Ni-Ag cocatalyst during the MB photodegradation reaction [28][29][30].…”
Section: Photodegradation Of Methylene Bluementioning
confidence: 99%